Formal employment and regional economic freedom in Mexico - Sánchez Juárez, Isaac (2020)
The paper aimed to answer whether economic freedom positively correlated with formal employment in Mexico. Data for the 2003-2015 period from the thirty-two federal entities and the northern and southern borders were used to create estimated panel data through fixed effects, random effects, and generalized method of moments (GMM). Economic freedom was negatively correlated with employment and elasticity was -0.04 for the thirty-two entities, while the elasticity of employment was positive (although statistically not significant) with respect to economic freedom for the northern border but negative (-2.20) for the southern region. Consequently, reducing government expenditure and taxes, as well as making the job market more flexible (greater economic freedom) are not the best policy options to create formal employment.